2011
DOI: 10.3174/ajnr.a2800
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural MR Imaging in Neuropsychiatric Disorders, Part 2: Application in Schizophrenia and Autism

Abstract: SUMMARY:During the past decade, the application of advanced MR imaging techniques in neuropsychiatric disorders has seen a rapid increase. Disease-specific alterations in brain function can be assessed by fMRI. Structural GM and WM properties are increasingly investigated by DTI and voxel-based approaches like VBM. These methods provide neurobiologic correlates for brain architecture and function, evaluation tools for therapeutic approaches, and potential early markers for diagnosis. Having provided insight in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…The social deficits may be related to frontal lobe dysfunction which plays a crucial role in social cognition network. The temporal region is responsible about language [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social deficits may be related to frontal lobe dysfunction which plays a crucial role in social cognition network. The temporal region is responsible about language [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Functional and structural imaging studies reported disruption of the white matter in autism [7][8][9][10]. There is reduced volume of the white matter at voxel based morphometry [11][12][13][14][15][16][17], abnormalities of choline and glutamate of white matter at MR spectroscopy [18] and decreased connectivity at functional MR imaging of autistic children [19].…”
Section: Introductionmentioning
confidence: 97%
“…74 Nonetheless, consistent diff erences in brain activation occur in regions that also show structural abnormalities, as highlighted in several recent reviews. [75][76][77] Findings from many studies have shown decreased activation in regions comprising the social brain network during tasks related to emotional processing or social cognition, including the amygdala, temporal-parietal junction, insula, and inferior frontal cortex; 71,[78][79][80][81][82][83][84] in frontostriatal circuitry in response to cognitive control tasks and repetitive behaviours; 75,[85][86][87][88] in language circuitry during communication tasks; [89][90][91] and in reward circuitry. [92][93][94][95] By contrast, abnormal increases in Series activation are found in response to irritants and direct gaze.…”
Section: Neural Activation and Functional Connectivitymentioning
confidence: 99%
“…Such relations between function and structure in parietal, occipital and temporal cortices were not affected (Cocchi et al 2014). The most characteristic change found in structural neuroimaging of schizophrenia patients is a reduction of grey matter volume, which tends to be more pronounced on the left side of the brain, especially in frontotemporal and limbic regions (Mueller et al 2012;Fujiwara et al 2015).…”
Section: Neuroimagingmentioning
confidence: 94%